Removal of AG 25 dye from aqueous solutions and treatment of real tannery wastewater by reusable magnetic iron oxide nanoparticles loaded with pomegranate pomace extract - Khelali, Ahlem; Benmahdi, Fatiha; Sahnoune, Derradji; Sami, Khettaf; Hacıosmanoğlu, Gül Gülenay; Akram, Sumia; Isinkaralar, Kaan; Siswanta, Dwi; Hosseini-Bandegharaei, Ahmad (Elsevier BV, 2025)
This study developed reusable magnetite iron oxide nanoparticles (Fe3O4@PGP-NPs) coated with pomegranate pomace extract (PGP) for the removal of Acid Green 25 (AG 25) dye and treatment of real tannery wastewater. The nanoparticles were characterized using FTIR, UV-Vis, XRD, FESEM/EDX, VSM, and BET techniques, revealing spherical Fe3O4 NPs with an average diameter of 20.30 nm, a BET surface area of 69 m2/g, and a magnetization value of 42.41 emu/g. Optimization via RSM-CCD identified optimal adsorption conditions: Fe3O4@PGP-NPs dosage of 2.2 g/L, contact time of 88 min, and dye concentration of 200 mg/L, achieving 99% removal efficiency. Adsorption followed the Langmuir model, with a monolayer capacity of 213 mg/g, and pseudo-second-order kinetics. Thermodynamic analysis confirmed the process was spontaneous and endothermic. When applied to tannery wastewater, Fe3O4@PGP-NPs achieved removal efficiencies of 98.87% for BOD5 and 97.40% for COD across treatment stages. Additionally, the nanoparticles maintained efficiency for up to five reuse cycles, demonstrating significant potential as a nanoadsorbent for dye removal and industrial wastewater treatment.